Factors that influence UiTM alumni’s attitudes towards PTPTN loan repayment / Maziha Abdul Kadir - Abdul Kadir, Maziha (Bachelor Of Business Administration (Hons) Marketing, 2015)
Perbadanan Tabung Pendidikan Tinggi Nasional (PTPTN) Education Loan Scheme is one of the organizations that provide education loans to students pursuing their studies in local institutions of higher learning (IPT). The research being conducted by the researcher is to explore the Factors That Influence UiTM Alumni’s Attitudes towards PTPTN Loan Repayment. The study was conducted in Kota Bharu, Kelantan and the target population is the UiTM alumni’s. The sample chosen for the research are 120 UiTM alumni’s that make an agreement with PTPTN. The researcher has used Statistical Package for the Social Science 20.0. Based on the findings, knowledge about loan repayment, awareness of loan repayment issues, perceptions of impact of loan repayment and parental influence show a significant relationship between UiTM alumni’s attitudes towards PTPTN loan repayment